Ultrasound-Guided Interstitial Laser Ablation for Thyroid Nodules Is Effective Only at High Total Amounts of Energy: Results From a Three-Year Pilot Study. (August 2013) - Gambelunghe, Giovanni; Fede, Raffaela; Bini, Vittorio; Monacelli, Massimo; Avenia, Nicola; D'Ajello, Michele; Colella, Renato; Nasini, Giovanni; De Feo, Pierpaolo
Objective . According to cross-sectional surveys, the prevalence of nontoxic nodular goiter appears to be higher in the adult population. Surgical intervention is indicated for the following: ( a ) progressive goiter growth, ( b ) compression of organs such as the trachea and esophagus, and ( c ) significant aesthetic disfigurement. Ultrasound-guided laser photocoagulation for the treatment of benign thyroid nodules is a viable alternative to traditional surgery. However, studies that have appeared in literature since the introduction of ultrasound-guided laser photocoagulation for the treatment of benign thyroid nodules report contradictory data concerning the energy required for nodule ablation. The aim of the present trial was to evaluate retrospectively the efficacy of percutaneous laser thermal ablation in 2 groups of patients, one treated with low, and the other with high, total amount of energy. Design . Forty euthyroid patients were treated with 1 session of percutaneous laser photocoagulation treatment at low (median = 71 J/mL; 20 patients) and high (median = 578 J/mL; 20 patients) energy. The volume of the nodules was measured by the same investigator, blinded for treatment, using the ellipsoid formula before treatment, at 2, 4, 8, and 30 weeks, and every 6 months for 3 years thereafter. Results . Thyroid nodule ablation is effective over time only if a sufficient amount of energy (>400-500 J/mL for the nodular tissue to be treated) is given, although it incurs proportionate side effects. Conclusions . Percutaneous laser thermal ablation is a viable alternative to traditional surgery for the treatment of benign nodular thyroid disease only if a sufficient amount of energy is delivered.